Bioremediation of Lead (Pb) Contaminated Soil Using Metaphire Javanica Earthworms and Eisenia Fetida Earthworms - Simanullang, Lady S.; Putro, Raden Kokoh Haryo; Nisa, Syadzadhiya Qouthrunada Zakiyayasin (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Soil contamination by heavy metals such as lead (Pb) is a serious environmental problem that can reduce soil quality and endanger living creatures. This study aims to analyze the bioaccumulation potential and remediation ability of Eisenia fetida earthworms and Metaphire javanica earthworms in Pb-contaminated soil. This study was conducted on a laboratory scale using four reactors, namely two reactors with earthworm treatment and one reactor with a control without treatment. The study was conducted over 40 days with sampling once every 10 days. The results showed that Eisenia fetida earthworms had the highest Pb reduction effectiveness of 67.19%, followed by Metaphire javanica earthworms at 48.80%. These results indicate that Eisenia fetida earthworms are more effective bioaccumulators than Metaphire javanica and have high potential as bioremediation agents for Pb-contaminated soil Contribution to Sustainable Development Goals (SDGs):SDG 15 (Life on Land) SDG 12 (Responsible Consumption and Production) SDG 3 (Good Health and Well-Being)